Evaluation and interpretation of growth, biomass productivity and lutein content of Chlorella variabilis on various media. Issue 3 (June 2020) - Loganathan, Bhalamurugan Gatamaneni; Orsat, Valerie; Lefsrud, Mark
Abstract: Physiological and biochemical changes along with lutein content of an under examined strain Chlorella variabilis was studied under controlled laboratory conditions. In this study, four different media including diluted dairy wastewater prepared artificially was utilized for optimizing its growth, biomass productivity and lutein content. The isolate of Chlorella variabilis was exposed to a continuous light intensity of 40 ± 3 μmol −1 m 2 s −1, temperature of 24 ± 2 °C and agitated on an orbital shaker at 90 rpm. The growth performance was evaluated in terms of optical density, chlorophyll content and cell count for a period of fourteen days and the pH was monitored regularly. In addition, the nutritional value, dry mass (carbohydrate, protein and lipid) and lutein content was evaluated at the end of sixteen days. The results showed that the Modified N8 medium as well as diluted synthetic dairy wastewater were the most productive culture that supported the growth of the microalga Chlorella variabilis with enhanced biomass productivity, nutritional value and lutein content when compared to other media thereby making it a potential candidate for use in poultry and aquaculture (∼74 % of protein) as well as for producing value added products specifically lutein. Furthermore, the study holds high importance as it reveals for the first time that the algal strain Chlorella variabilis could produce significant amount of lutein of 9.6 mg/g (9.6 g/kg) and could be the microalgal source of commercial lutein in the future.